Arcwise Connected Cone-Convex Functions and Mathematical Programming - Fu, J.Y.; Wang, Y.H. (Journal of optimization theory and applications, 2003)
The concept of arcwise connected cone-convex functions in topological vector spaces is introduced. Optimality conditions and duality theorems for a vector-valued nonlinear programming problem involving arcwise connected cone-convex functions are discussed.